Character Building of Prospective Students Through The Education And Learning System at Gontor For Girls Campus 2 - Abu Darda Abu Darda; Ayu Era Wardhani; Nur'aini Istiqomah; Rahmawati; Tazkiya Nurul Fauziah (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2026)
The formation of moral character is a fundamental aspect of Islamic education, which emphasizes the balance between intellectual development and moral development. This research focuses on sustainable and innovative efforts implemented in the Islamic education system at Pondok Modern Darussalam Gontor Putri Campus 2 to form the moral character of prospective students for the 2025–2026 academic year. This study uses a qualitative approach with a field study design. Participants include prospective students, teachers, and staf. Data is collected by observation, interviews, and documentation, then analyzed through data reduction, presentation, and conclusion drawn. The findings of the study show that continuous innovation in Islamic education at Gontor Putri Campus 2 is reflected in the integration of intramural, extracurricular, and daily habituation activities rooted in the local wisdom of Islamic boarding schools. Discipline, internalization of values, and exemplary behavior shown by Senior Teachers, Ustadzah and Mudabbirah are key factors in shaping the morals of karimah among prospective students. The study highlights that sustainable, locally-based innovation in Islamic education plays an important role in preparing the youngest generation who are moral, adaptive, and competitive to face the challenges of the times.